Vis??o de uma comunidade em vulnerabilidade socioambiental sobre a import??ncia dos servi??os de ??gua e esgoto - Bittencourt, Magali (2014)
The sanitation is intrinsically linked to health and its importance dates back to ancient cultures. Studies show that sanitation is one of the determinants of social vulnerability and the provision of treated water, and the collection and treatment of sewage are still insufficient in Brazil. This paper presents a research carried out in two stages in a community of high vulnerability, with poor access to treated water and no sewage. The objective was to find what its view on the sanitation before and after the access to these services and propose to the company that provides water and sewer services, a new performance to maximize these services. The statistical analysis of the survey data support the conclusion that, contrary to expectations , respondents did not consider the water and sewage services more important after their implementation. It is worth mentioning the fact that 100% of respondents consider unfair the price paid for the services and the differences between the opinions of men and women. The relevance of this work lies in the opportunity to use this knowledge to develop actions of sanitary and environmental education for the communities, so that they recognize its importance and become active agents in their conquest.